Design optimization of permanent magnet synchronous generators applied to a pilot exciter - Menezes, Gustavo Garbelini de (2024)
This dissertation presents the development of a design optimisation for permanent magnet synchronous generators applied to pilot exciters. The constant growth of worldwide electrical energy consumption has made the electrical generator market highly competitive, from small-scaled generator-diesel sets to large turbogenerators and synchronous hydro-generators. The preferred choice for power generation nowadays are wound-rotor synchronous generators, given their many advantages over permanent magnet and asynchronous generators. These machines require DC excitation to be supplied to their field winding to establish the primary magnetic field, typically regulated by an automatic voltage regulator. Among the various methods to supply power to the regulator, one of the most robust and reliable solutions is the use of a pilot exciter, which consists of a small permanent magnet synchronous generator mounted on the same shaft as the main generator. Given the additional machine required, the pilot exciter must be optimised to achieve maximum efficiency and torque density to remain a competitive solution. High efficiency ensures the delivery of the required power for the regulator with minimal energy losses, whereas increased torque density ensures maximum power output in a compact size. To accomplish this goal of a compact and efficient machine, firstly, a semi-analytical method for designing surface-mounted permanent magnet synchronous generators is developed and validated through finite element simulations. Two reluctance networks are then developed to obtain the no-load linkage flux and the armature reaction, which are essential for the design and for accurately calculating the terminal voltage. After validating their results, these magnetic circuits are integrated into the design procedure, resulting in an optimisation-oriented electromagnetic model that enables the precise and time-efficient optimisation of surface-mounted permanent magnet synchronous generators. A Pareto front is generated to evaluate the trade-off between efficiency and torque density, guiding the selection of an optimal solution that balances both objectives. Finally, the optimised permanent magnet generator is validated with finite element simulations, demonstrating the accuracy of the proposed method.